2006
DOI: 10.1177/00224669060400030201
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trends in the National Demand, Supply, and Shortage of Special Education Teachers

Abstract: With a focus on both teacher quality and quantity at the national level, this research examined longterm trends in the demand, supply, and shortage of special education teachers for 16 school years, from 1987/1988 through 2002/2003. These trends were based on data published in annual reports to Congress on the implementation of the Individuals with Disabilities Education Act by the Office of Special Education Programs, U.S. Department of Education. Rapid growth in teacher demand for students with disabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 6 publications
0
61
0
Order By: Relevance
“…Indicators, Explanations, and Impacts For well over two decades as the demand for special education teachers (SETs) was increasing in response to rapid growth in the numbers of students with disabilities (SWD), the field struggled to address shortages of qualified teachers to satisfy this demand (Boe, 2006). 2 The…”
Section: Variability In Demand For Special Education Teachersmentioning
confidence: 99%
See 3 more Smart Citations
“…Indicators, Explanations, and Impacts For well over two decades as the demand for special education teachers (SETs) was increasing in response to rapid growth in the numbers of students with disabilities (SWD), the field struggled to address shortages of qualified teachers to satisfy this demand (Boe, 2006). 2 The…”
Section: Variability In Demand For Special Education Teachersmentioning
confidence: 99%
“…Analyses of these trend data from OSEP and from the National Center for Education Statistics (NCES) by Boe and colleagues (e.g., Boe, 2006;Boe & Cook, 2006;Boe, Cook, & Sunderland, 2007; have demonstrated that increases in demand outstripped the supply of qualified SETs resulting in acute and chronic shortages-shortages that persisted in spite of OSEP's longstanding commitment to and investment in personnel preparation (West & Whitby, 2008).…”
Section: Variability In Demand For Special Education Teachersmentioning
confidence: 99%
See 2 more Smart Citations
“…Both exist to train preservice teachers. Within the United States, shortages in special educators over the past two decades (Boe, 2006) have led to the development of AC programs. Questions have been raised about the quality of these forms of training programs.…”
Section: Training In Special Educationmentioning
confidence: 99%